Exploring environmental policy adoption enablers for indoor air quality management in higher educational institutions in South Africa - Mpho Ndou; Clinton Aigbavboa (Frontiers in Built Environment, 2023)
Purpose: This study seeks to investigate the extent to which the indoor air quality (IAQ) management of higher educational institutions (HEIs) in South Africa could be improved through the appropriate implementation of environmental policy adoption enablers. Multiple challenges have been documented to the improvement of IAQ standards in HEIs. However, an alternative to the management of IAQ is possible through environmental behavioral change.Research Methodology: A philosophical stance of post-positivism influences the adoption of a quantitative research approach for this study. Primary data on the views shared by various academic and administrative staff employed by HEIs across South Africa were collected using a closed-ended questionnaire survey. A literature review uncovered 16 influential environmental policy adoption enablers that could further the objective of the study. A four-phase data analytical approach was adopted to interpret the empirical data through screening and reliability assessment, together with descriptive and inferential statistical evaluations, to ascertain the influence held by the surveyed policy adoption enablers on improving the management of IAQ in HEIs.Results: The inferential statistical evaluation using exploratory factor analysis revealed three crucial environmental policy adoption metrical approaches (stakeholder dialogue, institutional commitment, and policy composition) to the management of IAQ in HEIs.Discussion: From a practical perspective, the administrative council of HEIs could consider the identified policy adoption enablers as a catalyst for pro-environmental behavior and the management of IAQ in all respective institutions. Theoretically, this study contributes to the body of knowledge by providing factors associated with environmental policy adoptions for IAQ management and laying the groundwork for future research in environmental behavior, this has been lacking in previous IAQ studies and current environmental management discourse. As an instrumental enabler, the identified policy adoption approaches could inform any existing or new institutional policy adoption initiative aimed at improving current individuals’ perception of workplace comfort, satisfaction, and performance directly associated with their indoor environmental conditions.